The effect of minimal dietary changes with raisins in NAFLD patients with non-significant fibrosis: a randomized controlled intervention12. Issue 11 (6th October 2016) - Kaliora, Andriana C.; Kokkinos, Alexander; Diolintzi, Anastacia; Stoupaki, Maria; Gioxari, Aristea; Kanellos, Panagiotis T.; Dedoussis, George V. Z.; Vlachogiannakos, Jiannis; Revenas, Constantinos; Ladas, Spiros D.; Karathanos, Vaios T.
Abstract : Aiming at investigating the potential effect of minimal dietary changes in NAFLD patients with non-significant fibrosis, 55 patients with NAFLD were enrolled in a randomized controlled clinical trial. Abstract : Aiming at investigating the potential effect of minimal dietary changes in NAFLD patients with non-significant fibrosis, 55 patients with NAFLD were enrolled in a randomized controlled clinical trial. Patients were assigned into two isocaloric dietary treatment groups for 24 weeks: (a) nutritional counseling (Control arm, N = 27), (b) nutritional counseling with currants included (two fruit servings, 36 g per day), substituting snacks of similar caloric content (Currant arm, N = 28). Clinical tests, anthropometrics, inflammatory and oxidative stress markers were conducted pre- and post-intervention. A total of 50 patients completed the trial. Significant differences between the two arms post-intervention were observed in fasting glucose and in IL-6 levels, these being significantly decreased only in Currant patients. Body weight, BMI, HbA1c, CRP and EUS values decreased in both arms, differences being insignificant between the two arms post-intervention. Participants in the Currant arm had significantly reduced total body fat, WC and trunk fat. Ultrasound scanning improved significantly in patients snacking currants daily. Also, volunteers enrolled in the Currant arm showed a reduced intake of saturated fatty acids. Because BW regulation has been officially recognised as a treatment approach in NAFLD an additional analysis was repeated in patients adhering to this. Post-intervention, the decrease in IL-6 and in fasting glucose was significantly higher in Currant patients who lost BW compared to their counterparts in the Control arm. Conclusively, minimal modifications in snacking choices, such as the inclusion of dried grapes in diet, are beneficial in NAFLD patients with non-significant fibrosis.